The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1242/jcs.155424
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of endocytosis prevent Wnt/Wingless signalling by reducing the level of basal β–Catenin/Armadillo

Abstract: A key step in the canonical Wnt signalling pathway is the inhibition of GSK3β, which results in the accumulation of nuclear β-catenin (also known as CTNNB1), and hence regulation of target genes. Evidence suggests that endocytosis is required for signalling, yet its role and the molecular understanding remains unclear. A recent and controversial model suggests that endocytosis contributes to Wnt signalling by causing the sequestration of the ligand–receptor complex, including LRP6 and GSK3 to multivesicular bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Consistent with Clathrin's reported role in mitotic spindle organization (29), knockdown of Clathrin HC led to reduced cell proliferation. In addition, Gagliardi and colleagues reported a decrease in levels of multiple Wnt pathway proteins with or without Wnt stimulation in the presence of endocytosis inhibitors and suggested that inhibition of endocytosis may trigger degradation of multiple proteins through an unknown mechanism (39). Finally, disruption of Dynamin, which has been employed to inhibit endocytosis, could lead to pleiotropic effects and confound study conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Clathrin's reported role in mitotic spindle organization (29), knockdown of Clathrin HC led to reduced cell proliferation. In addition, Gagliardi and colleagues reported a decrease in levels of multiple Wnt pathway proteins with or without Wnt stimulation in the presence of endocytosis inhibitors and suggested that inhibition of endocytosis may trigger degradation of multiple proteins through an unknown mechanism (39). Finally, disruption of Dynamin, which has been employed to inhibit endocytosis, could lead to pleiotropic effects and confound study conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work indicated that Axin is sequestered in multivesicular bodies (MVBs) that form following Wnt stimulation [48]; however a subsequent study revealed that MVB formation is not required for Wnt pathway activation in Drosophila [49]. The membrane-proximal Axin puncta we have observed are unlikely to represent MVBs, since these puncta are found in the absence of Wnt exposure; however, the presence of these puncta may suggest that Axin associates with other types of vesicles juxtaposed with the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, evidence that endocytosis appears to be an obligate step for Wnt signal transduction (Bilic et al, 2007; Blitzer & Nusse, 2006), as is known for many other signaling pathways (Goh & Sorkin, 2013; Haglund & Dikic, 2012), raises the possibility that cadherins may impact Wnt signaling by controlling Wnt receptor complex internalization into signalosomes (Bilic et al, 2007). In this regard, recent studies show that Wnt receptor complex activation can promote the sequestration of GSK3 into multivesicular bodies (Taelman et al, 2010) (although perhaps not in flies; Gagliardi, Hernandez, McGough, & Vincent, 2014), leading to β-catenin stabilization and signaling, where the cadherin and p120 ctn appear required for this process (Vinyoles et al, 2014). Given that the cadherin/catenin complex is fundamental not only for cell–cell adhesion but for basic membrane dynamics (Abreu-Blanco, Verboon, Liu, Watts, & Parkhurst, 2012; Schepis, Sepich, & Nelson, 2012), it may not be surprising to find these examples of the cadherin/catenin complex being both required for and inhibitory to Wnt/β-catenin signaling.…”
Section: The Cadherin–catenin Complex As Both a Potentiator And Anmentioning
confidence: 99%